Structure-gelation research on gallate analogs and xyloglucan by rheology, thermal analysis and NMR. (January 2016) - Yan, Youyu; Takemasa, Makoto; Zhao, Chunfang; Yu, Longjiang; Nishinari, Katsuyoshi
Abstract: The influence of molecular structure of gallate analogs on the gelation behavior of xyloglucan in the presence of gallate analogs was investigated by rheology and differential scanning calorimetry (DSC) and NMR. We found that solutions of tamarind seed xyloglucan (TSX) in the presence of gallate analogs such as Epigallocatechin gallate (EGCg), Epicatechin gallate (ECg), Gallic acid (GA), methyl, ethyl, propyl gallate (abbreviated m GA, e GA and p GA respectively), pyrogallol, p-, m- and 3, 5-di-hydroxybenzoic acids all could induce a thermo-reversible gelation and form gels of different stiffnesses, but (−)-Gallocatechin gallate (GCg), (−)-Epigallocatechin (EGC), (−)-Epicatechin (EC), benzoic acid, salicylic acid could not. By constructive induction and analogy a possible conclusion could be deduced that on the basis of sufficient mutual solubility, a structure analogue to galloyl moiety in certain chemicals is the critical structure feature which induces the gelling of xyloglucan, a decrease in hydroxyl group number led to weakened gel strength but increased critical gelling concentration, if removing of acetoxyl group from the gallate ring would significantly reduce the gelation potency. Furthermore, the relative position of acetoxyl and hydroxyl group, as well as the branched side group linked to the acyloxy of gallate analogs both affected the gelling behavior. These conclusions were also further supported by visual, rheological, DSC observations and NMR. Graphical abstract: Thermal scanning rheology and DSC on cooling at 0.5 °C/min for xyloglucan with GA, p GA, e GA and m GA. Highlights: Effect of structure of gallate analogs on the gelation of TSX was studied. Galloyl moiety are the critical structure feature which induces TSX gelling. Conformation and acetoxyl group corresponding to gallate ring affect gelation. Other factors the relative position of acetoxyl and hydroxyl group etc also affect.